POLITICAL AND COMMUNAL CONFLICT ON MURDER CASES IN INDIA - Sonajirao Garje, Balasaheb; Vijaya Singh, Atibha; Yadav, Jitendra (International Journal of Psychosocial Rehabilitation, 2020)
Conflicts that resulted in murder were examined in detail, as well as the formal and informal options available to and selected by the parties involved, as well as how a crime came to be committed, as well as the role played by criminal justice systems and any other relevant elements. Three years of data from the National Crime Records Bureau (NCRB) reveal a modest but practically consistent rise of statistics related to violent categories, with the numbers of crimes against bodies exceeding crimes against property and murder statistics indicating a little incline despite this. According to the 2013 Global Homicide Study, a substantial majority of killings are the result of interpersonal conflict, with India accounting for the highest percentage of homicides linked to interpersonal conflict at 48 percent (UNODC, 2014)